The interior plan : concepts and exercises - Rengel, Roberto J. (2016)
"This introductory-level text introduces students to the planning of interior environments, addressing both the contents of the environments and the process of interior space planning. Topics include the making of rooms, the design of effective spatial sequences, functional relationships among project parts, arrangement of furniture, planning effective circulation systems, making spaces accessible, and designing safe environments with efficient emergency egress systems. Exercises throughout the book facilitate learning by encouraging students to apply ideas and concepts immediately after reading about them. This second edition features logically re-organized content with coverage on accessibility and universal design throughout, providing for a more intuitive read. It also features new original artwork by the author and a new glossary for quick look-up of terms. Finally, there are new exercises that engage students and test their ability to apply what they have learned"--
Keywords: Interior architecture -- Textbooks; ARCHITECTURE / Interior Design / General